Exploring the Optimal Factor Structure of the Five Facet Mindfulness Questionnaire: Associations Between Mindfulness Facets and Dimensions of Psychopathology. Issue 6 (24th October 2022) - Diehl, Joseph M.; Rodriguez-Seijas, Craig; Thompson, Justine S.; Dalrymple, Kristy; Chelminski, Iwona; Zimmerman, Mark
Abstract: Recent studies of the Five Facet Mindfulness Questionnaire (FFMQ) and its condensed version (FFMQ-SF) fail to replicate the initially proposed five-factor structure in clinical samples. Failure to adequately understand the dimensionality of common mindfulness measures within clinical samples, therefore, represents an important gap in the current literature. The increasing popularity of mindfulness-based interventions warrants further investigation of differential associations between facets of mindfulness and different forms of psychopathology. We examined (a) the underlying structure of the FFMQ and FFMQ-SF, and (b) associations between FFMQ and FFMQ-SF facets and dimensions of psychopathology (i.e., internalizing and substance use disorders) in two large clinical samples ( N = 2, 779). Results from bass-ackwards analyses suggested similarly defensible five- and six-factor model solutions in terms of fit. The five-factor model was optimal when factoring in parsimony. Exploratory structural equation modeling revealed that all FFMQ facets with the exception of observe were negatively associated with the internalizing factor. Associations with substance use disorders were more complex. In both samples, five-factor FFMQ and FFMQ-SF models were determined to best represent these data. Whereas deficits in all FFMQ facets with the exception of observe correspond with lower internalizing psychopathology, a more nuanced association was observed with substance use disorders.